O Jerusalem! - Sabella, Bernard; Tamārī, Salīm; Safieh, Afif; Arsenian Carmi, Nora (Christian Voices from the Holy Land, 2000)
(...) Safieh, Afif: Rally for the right of return. - S. 6-8. Safieh, Afif: On Jerusalem. - S. 9-17. Sabella, Bernard: From the earthly to the heavenly. Unmet challenges in Jerusalem. - S. 18-22. Arsenian Carmi, Nora: O, Jerusalem! - S. 23-29. Tamari, Salim: Jerusalem's Ottoman modernity. The times and lives of Wasif Jawhariyyeh. - S. 30-37. Cotran, Eugene: Why has Oslo failed? A legal point of view. - S. 38-42. Safieh, Afif: Out of Jerusalem? - S. 43-46